2001
DOI: 10.1002/mus.1171
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral neuropathy in young‐old and old‐old patients

Abstract: Diabetes is said to account for most cases of neuropathy in the elderly. We reviewed records of 223 young-old (65-79 years) and 77 old-old (>or=80 years) patients referred for evaluation of neuropathic symptoms over a 9-year period. We prospectively validated our findings in 102 consecutive elderly (77 young-old) patients receiving intensive evaluation for neuropathy. Diabetes was the most common cause of neuropathy (41%), but was less common in the old-old (25% versus 46%, P < 0.001). Idiopathic neuropathies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
2
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 22 publications
6
32
2
3
Order By: Relevance
“…In referred populations, however, idiopathic peripheral neuropathy is more common with increasing age. For example, Verghese et al 39 found that 39% of those aged Ն80 but only 9% of those aged 65 to 79 were classified as idiopathic.…”
Section: Prevalence and Significancementioning
confidence: 99%
“…In referred populations, however, idiopathic peripheral neuropathy is more common with increasing age. For example, Verghese et al 39 found that 39% of those aged Ն80 but only 9% of those aged 65 to 79 were classified as idiopathic.…”
Section: Prevalence and Significancementioning
confidence: 99%
“…Patients with pre-existing conditions known to cause neuropathy (identified in the history or during basic screening by their primary care physician/during a preceding clinic appointment), were excluded from the current analysis. This explains the relatively high incidence of idiopathic neuropathy in our series (41%), compared to some previous studies, some of which, for their part, took into account all cases analyzed including genetic and inflammatory [12][13][14] which were intentionally excluded from our analysis. We considered patients with IGT amongst those with non-idiopathic neuropathy, as we believe the body of available literature currently suggests this may represent a frequent cause of distal axonal neuropathy [15].…”
Section: Discussionmentioning
confidence: 60%
“…The incidence of idiopathic axonal neuropathy in elderly people is quite significant. Verghese et al [16] found an average incidence of 27.2 % among 402 subjects older than 65 years, 12.5 % in those younger than 75 years, 23.3 % in those younger than 84 years and 45.9 % in those older than 85 years. Interestingly, CblD was present in only 1.3 % of 213 subjects younger than 75 years and in 0.7 % of 142 subjects younger than 85 years.…”
Section: Discussionmentioning
confidence: 97%